COVID-19 pandemic and crisis management in the Republic of Croatia - Mikac, Robert (Array, 2020)
The COVID-19 pandemic and the crisis that has affected all parts of the world, all industries and business processes, have significantly changed the usual way of life, introduced society to the ‘new normal’ and imposed the need for crisis management. Many organizations and countries were not ready for the crisis and consequently are suffering great consequences. The aim of this paper is to analyze how Croatia responded to this crisis from the aspect of the existing normative framework for crisis management and the operational solutions in practice, as well as to explore the role of the Government of the Republic of Croatia and its leaders in strategic decision making and interpretation of the crisis, and the extent to which homeland security and civil protection systems were put in function in managing the crisis. As an additional aim, the paper intends to mark a certain number of contradictions, controversies and paradoxes that arose during the crisis, as well as certain observations that can serve for further analysis and elements in the lessons learned process.